Motivational interviewing : helping people change and grow - Miller, William R. (William Richard); Rollnick, Stephen, 1952- (New York, NY : The Guilford Press, a division of Guilford Publications, Inc., 2023)
'Now in a fully rewritten fourth edition, this is the authoritative presentation of motivational interviewing (MI), the powerful approach to facilitating change. It has been updated and streamlined to be even more user-friendly as a practitioner guide and course text. MI originators William R. Miller and Stephen Rollnick elucidate the four tasks of MI--engaging, focusing, evoking, and planning--and vividly demonstrate what they look like in action. A wealth of vignettes and interview examples illustrate the dos and don'ts of successful implementation in diverse contexts. The book reviews the evidence base for the approach and covers ways to assess the quality of MI. The companion website provides reflection questions, annotated case material, and additional helpful resources. New to This Edition *Most of the book is entirely new. *Addresses the breadth of MI applications not only in counseling and psychotherapy, but also in health care, education, coaching, management, and other contexts. *Discusses delivering MI remotely, simple versus complex affirmations, strategic use of directional questions, ethical considerations, and other new or expanded topics. *Increased emphasis on using MI throughout a client's process of change and growth, not just in the preparatory stage. Pedagogical Features *New or updated online materials, including reflection questions and annotated cases. *Key points at the end of each chapter. *'Personal Perspective' and'For Therapists' boxes in every chapter. *Extended bibliography and quick-reference glossary. *New self-assessment tool that targets the component skills of MI. This book is in the Applications of Motivational Interviewing series, edited by Stephen Rollnick, William R. Miller, and Theresa B. Moyers.'--
I. Helping People Change and Grow -- 1. The Mind and Heart When Helping -- 2. What Is Motivational Interviewing? -- 3. A Flowing Conversation -- II. Practicing Motivational Interviewing -- 4. Engaging:'Can We Walk Together?' -- 5. Focusing:'Where Are We Going?' -- 6. Evoking:'Why Would You Go There?' -- 7. Planning:'How Will You Get There?' -- III. A Deeper Dive into Motivational Interviewing -- 8. Deeper Listening -- 9. Focusing: A Deeper Dive -- 10. Evoking: Cultivating Change Talk -- 11. Offering Information and Advice -- 12. Supporting Persistence -- 13. Planting Seeds -- 14. Responding to Sustain Talk and Discord -- 15. Practicing Well -- IV. Learning and Studying Motivational Interviewing -- 16. Learning Motivational Interviewing -- 17. Learning from Conversations about Change -- 18. Studying Motivational Interviewing -- Glossary of Motivational Interviewing Concepts.
Includes bibliographical references and index.
WorldCat record variable field(s) change: 050
Keywords: Compulsive behavior -- Treatment; Substance abuse -- Treatment; Substance abuse -- Patients -- Counseling of; Compulsive behavior -- Patients -- Counseling of; Motivation (Psychology); Interviewing in psychiatry; Behavior Therapy -- methods; Motivational Interviewing. 0 (DNLM)D062405; Motivation; Behavior, Addictive -- therapy; Comportement compulsif -- Traitement; Abus de substances psychoactives -- Traitement; Comportement compulsif -- Patients -- Counseling; Motivation (Psychologie); Entretiens (Psychiatrie); Compulsive behavior -- Treatment; Interviewing in psychiatry; Motivation (Psychology); Substance abuse -- Patients -- Counseling of; Substance abuse -- Treatment